2021
DOI: 10.1136/heartjnl-2021-319597
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre comparative analysis of long-term outcomes after aortic valve replacement in children

Abstract: ObjectiveThe ideal valve substitute for surgical intervention of congenital aortic valve disease in children remains unclear. Data on outcomes beyond 10–15 years after valve replacement are limited but important for evaluating substitute longevity. We aimed to describe up to 25-year death/cardiac transplant by type of valve substitute and assess the potential impact of treatment centre. Our hypothesis was that patients with pulmonic valve autograft would have better survival than mechanical prosthetic.MethodsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…A significant number of recent studies have shown that the Ross procedure boasts excellent overall transplant-free survival, aortic valve reoperation-free survival, and event-free survival [ 9 - 11 ]. Moreover, some reports have highlighted the superiority of the Ross procedure in terms of survival and freedom from reoperation or event, compared to mechanical AVR in children and young adults [ 12 - 14 ]. However, the Ross procedure is technically challenging, carries a long-term risk of autograft dilatation and subsequent failure, and has a high likelihood of necessitating reoperation or reintervention in the right ventricular outflow tract [ 11 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant number of recent studies have shown that the Ross procedure boasts excellent overall transplant-free survival, aortic valve reoperation-free survival, and event-free survival [ 9 - 11 ]. Moreover, some reports have highlighted the superiority of the Ross procedure in terms of survival and freedom from reoperation or event, compared to mechanical AVR in children and young adults [ 12 - 14 ]. However, the Ross procedure is technically challenging, carries a long-term risk of autograft dilatation and subsequent failure, and has a high likelihood of necessitating reoperation or reintervention in the right ventricular outflow tract [ 11 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the overall transplant-free survival rate at 10 years was 90%, which aligns with the results of previous studies. Earlier studies identified factors associated with death or transplantation, including younger age, the need for an annular enlargement procedure, and associated congenital heart diseases [ 12 , 14 , 19 ]. However, in our study, we were unable to identify any factors associated with death or transplantation.…”
Section: Discussionmentioning
confidence: 99%